Legal Protection for Consumers in the Implementation of Electronic Trading Contracts - Saragih, Yasmirah Mandasari; Dahris Siregar; Arianus Halawa; Adilman Reliance Lawolo; Arianto Lase; Ardiman Waruwu; Heronimus Halawa; Yuniel Putra Hulu (PT Inovasi Pratama Internasional, 2022)
Destination from study this for knowing like what procedure transact sell buy in maintenance system electronic through online application and aim also for knowing like what analysis protection law moment maintenance transaction sell buy via the internet. Method approach taken is method approach normative juridical emphasis on aspect regulation source legislation the data from the secondary data it consists of from ingredient primary laws , materials law secondary and ingredient law tertiary with method data collection with through method studies library (library research ). Data analysis was performed start from hierarchy regulation legislation and opinion para expert . Results study this form how procedure transaction electronic through application topedia , open lapak , shoppe and so on . Source law contract electronics , rights and obligation perpetrator effort and buyers , developments transaction electronic as well as settlement dispute .